2005
DOI: 10.1074/jbc.m501164200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pathophysiological Mechanism for Osteoporosis Suggested by an in Vivo Gene Expression Study of Circulating Monocytes

Abstract: Bone mineral density (BMD) is a major risk factor for osteoporosis. Circulating monocytes may serve as early progenitors of osteoclasts and produce a wide variety of factors important to bone metabolism. However, little is known about the roles of circulating monocytes in relation to the pathophysiology of osteoporosis. Using the Affymetrix HG-U133A GeneChip® array, we performed a comparative gene expression study of circulating monocytes in subjects with high and low BMD. We identified in total 66 differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
128
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(134 citation statements)
references
References 53 publications
4
128
1
1
Order By: Relevance
“…Among genes involved in immune response we observed upregulation of chemokine receptor 2 (Ccr2). It has been suggested that upregulation of another chemokine receptor, CCR3 in circulating monocytes of individuals with low BMD may facilitate both the access of monocytes to the bone microenvironment and their subsequent differentiation into osteoclasts (6). Since it was shown that chemokine receptors CCR2b and CCR4 were potently induced by RANKL (22), we suggest that increased expression of Ccr2 was rather a consequence of elevated RANKL production due to increased bone remodeling, than a direct cause of increased bone resorption.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Among genes involved in immune response we observed upregulation of chemokine receptor 2 (Ccr2). It has been suggested that upregulation of another chemokine receptor, CCR3 in circulating monocytes of individuals with low BMD may facilitate both the access of monocytes to the bone microenvironment and their subsequent differentiation into osteoclasts (6). Since it was shown that chemokine receptors CCR2b and CCR4 were potently induced by RANKL (22), we suggest that increased expression of Ccr2 was rather a consequence of elevated RANKL production due to increased bone remodeling, than a direct cause of increased bone resorption.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, three genes with putative role in bone metabolism, namely CCR3 (chemokine receptor 3), HDC (histidine decarboxylase, i.e. the histamine synthesis enzyme), and GCR (glucocorticoid receptor) were upregulated in circulating monocytes of subjects with low BMD (6). In addition, increased production of IL-1 and tumour necrosis factor α (TNF-α) has been observed in circulating mononuclear cells in women with postmenopausal osteoporosis (7,8).…”
mentioning
confidence: 90%
“…We suggest, however, that the use of multiple time points and a rather stringent filtering procedure decreased the likelihood of identified false positives. Our results nevertheless suggest that careful validation on a different platform remains an absolute necessity (27).…”
Section: Discussionmentioning
confidence: 95%
“…It was cautioned that the analyses had limited power and that effect sizes were very modest, reinforcing the belief that there are many more sequence variants relevant to osteoporosis to be identified. (13,29) Liu and colleagues (31) used microarray technology to study gene expression in circulating blood monocytes from women with high or low BMD. While circulating blood cells are easily obtainable and represent an attractive source of biologic material for diagnostic purposes, they do not reflect local processes in bone, the primary site of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%